Resposta :
Resposta:
a) 2x + y = 7 2 × 5 + y = 7
x - y = 8 10 + y = 7 S = (5, -3)
3x = 15 y = 7 - 10
x = 15/3 y = -3
x = 5
b) x - y = 5 x - y = 5 7 + y = 9
3 × (x + y) = 27 x + y = 9 y = 9 - 7
x - y = 5 2x = 14 y = 2 S = (7,2)
3x + 3y = 27(:3) x = 14/2
x = 7
c) 2x - y = 7 x + 5 × 1 = -2
x + 5y = -2 x + 5 = -2
2x - 4 = 7 x = -2 - 5 S = (-7, 1)
-2x - 10 y = 4 x = -7
-11y = 11(-1)
11y = -11
y = -11/11
y = 1
d)3a = 16 + b -9a+3b = -48 3 × 11/2 - b 2(a + 1) - 3(b + 2) =a a - 3b = 4 33/2 - b =16
3a - b =16 -8a = -44(-1) 33-2b/2=32/2
2a + 2 - 3b - 6-a=0 8a = 44 -2b = 32 - 33
3a - b = 16 a = 44/8 ÷ 4 -2b = -1
a - 3b - 4 = 0 a = 11/2 2b = 1
3a - b = 16(-3) b = 1/2
a - 3b = 4
S = (11/2, 1/2)
Resposta:
1) a) S= (5,-3)
Resolução:
[tex]2x + y = 7 \\ x - y = 8 \\ 3x = 15 \\ x = \frac{15}{3} \\ x= 5[/tex]
[tex]2 \times 5 + y = 7 \\ 10 + y = 7 \\ y = 7 - 10 \\ y = - 3[/tex]
b) S= (7,2)
Resolução:
[tex]x - y = 5 \\ 3x(x + y) = 27 \\ x - y = 5 \\ 3x + 3y = \frac{27}{3} \\ x - y = 5 \\ x + y = 9 \\ 2x = 14 \\ x = \frac{14}{2} \\ x = 7[/tex]
[tex]7 + y = 9 \\ y = 9 - 7 \\ y = 2[/tex]
c) S= (3,-1)
Resolução:
[tex]x + 5(2x - 7) = - 2 \\ x + 10x - 35 = - 2 \\ 11x = 33 \\ x = \frac{33}{11} \\ x = 3[/tex]
[tex]2x - y = 7 \\ x + 5y = - 2 \\ 2x - y = 7 \\ x = - 2 - 5y \\2x - y = 7 \\ 2( - 2 - 5y) - y = 7 \\ - 4 - 10y - y = 7 \\ - 11y = 7 + 4 \\ - 11y = 11 \\ y = \frac{ - 11}{11} \\ y = - 1[/tex]
d) S= (11/2, 1/2)
[tex]3a = 16 + b \\ 2(a + 1) - 3(b + 2) = a \\ 3a - b = 16 \\ 2a + 2 - 3b - 6 - a = 0 \\ 3a - b = 16 \\ - 3b - 4 = 0 \\ 3a - b = 16( - 3) \\ a - 3b = 4 \\ - 9a + 3b = - 48a - 3b = 4 \\ - 8a = - 44( - 1) \\ 8a = 44 \\ a = \frac{44}{8} \div 4 \\ a = \frac{11}{2} [/tex]
[tex]3. \frac{11}{2} - b \\ \frac{33}{2} - b = 16 \\ 33 - \frac{2b}{2} = \frac{32}{2} \\ - 2b = 32 - 33 \\ - 2b = - 1( - 1) \\ 2b = 1 \\ b = \frac{1}{2} [/tex]
Explicação passo-a-passo:
Espero ter ajudado!